1992
DOI: 10.1161/01.str.23.11.1595
|View full text |Cite
|
Sign up to set email alerts
|

Ischemia-induced extracellular release of serotonin plays a role in CA1 neuronal cell death in rats.

Abstract: Background and Purpose: Serotonin, via 5-HT 2 receptors, exerts an excitatory effect on CA1 neurons and may play a role in ischemia-induced excitotoxic damage. To evaluate the role of serotonin in ischemia, both neurochemical and histopathological studies were performed.Methods: Neurochemical studies included rats that were subjected to 12.5 or 20 minutes of normothermic ischemia by two-vessel occlusion plus hypotension, and extracellular serotonin levels were measured in the hippocampus (12.5 minutes' ischemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
30
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(31 citation statements)
references
References 56 publications
1
30
0
Order By: Relevance
“…Given that serotonin plays a pathological role in a number of low blood flow conditions [2][3][4], the properties of some serotoninergic receptor agonists and antagonists as putative neuroprotectants have been explored. The antagonists of 5-HT 2 receptors such as ritanserin, ketanserin and mianserin were shown to reduce the volume of the brain infarct, to improve behavioral performance, or to have beneficial effects on the local cerebral blood flow in models of global and forebrain ischemia and in models of permanent focal ischemia in rats and gerbils [7][8][9][10][11][12][13]. However, data about the effects of the 5-HT 2 receptor antagonists in models of transient focal ischemia are lacking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that serotonin plays a pathological role in a number of low blood flow conditions [2][3][4], the properties of some serotoninergic receptor agonists and antagonists as putative neuroprotectants have been explored. The antagonists of 5-HT 2 receptors such as ritanserin, ketanserin and mianserin were shown to reduce the volume of the brain infarct, to improve behavioral performance, or to have beneficial effects on the local cerebral blood flow in models of global and forebrain ischemia and in models of permanent focal ischemia in rats and gerbils [7][8][9][10][11][12][13]. However, data about the effects of the 5-HT 2 receptor antagonists in models of transient focal ischemia are lacking.…”
Section: Discussionmentioning
confidence: 99%
“…However, data for their use as neuroprotective drugs in human acute cerebrovascular disorders are lacking. 5-HT 2 receptor antagonists have been shown to have neuroprotective properties in models of global and forebrain transient ischemia [7][8][9][10]. However, in models of focal ischemia, the data about their effects are not sufficient (obtained only in models of permanent focal ischemia) and contradictory [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…3134 Furthermore, serotonergic denervation partially protects the striatum from kainic acid-mediated damage. 26 In a previous report from our laboratory, Globus et al 23 reported the involvement of serotonin in ischemic neuronal dam-age in the setting of transient global forebrain ischemia. Therefore, it is possible that a selective 5-HT 2 receptor antagonist might have a protective effect against ischemic damage in focal ischemia.…”
mentioning
confidence: 91%
“…Previous studies from our laboratory have examined the effects of preischemic administration of 5-HT 2 antagonist on ischemic outcome. 23 In this study, ritanserin was administered after middle cerebral artery occlusion, and systemic blood pressure and cerebral blood flow (CBF) were measured during the ischemic period.…”
mentioning
confidence: 99%
“…Excessive release of glutamate is believed to play an important role in the development of the neuronal damage. However, it has also been shown that extracellular serotonin level is increased in hippocampus during cerebral ischaemia (Globus et al 1992). Several studies have shown the possibility of protecting neurones from ischaemic damage by stimulation or inhibition of different serotonergic receptors.…”
mentioning
confidence: 99%